ADHESIVE SYSTEM AFFECTS REPAIR BOND STRENGTH OF RESIN COMPOSITE - Özgür IRMAK; Özge ÇELIKSÖZ; Begüm YILMAZ; Batu Can YAMAN (Istanbul University, 2017)
Purpose: This study evaluated the effects of different adhesive systems on repair bond strength of aged resin composites. Materials and Methods: Ninety composite discs were built and half of them were subjected to thermal aging. Aged and non-aged specimens were repaired with resin composite using three different adhesive systems; a two-step self-etch adhesive, a two-step total-etch adhesive and a one-step self-etch adhesive; then they were subjected to shear forces. Data were analyzed statistically. Results: Adhesive type and aging significantly affected the repair bond strengths (p<0.0001). No statistical difference was found in aged composite groups repaired with two-step self- etch or two-step total-etch adhesive. One-step self-etch adhesive showed lower bond strength values in aged composite repair (p<0.0001). Conclusion: In the repair of aged resin composite, two-step self-etch and two-step total-etch adhesives exhibited higher shear bond strength values than that of one-step self-etch adhesive.